Strategic Communication Techniques in Political Marketing Lobbying - Emrus, Emrus (IJOSMAS, 2022)
The aim of this study wants to analyze the Political marketing lobbying needs communication strategies and techniques to influence the map of audience cognition to form the public opinion favorable for parties in carrying out political activities/movements/struggles. These events need to be excellent political marketing lobby communication strategies and techniques to build people/public trust in political actors and their political struggles. The trust encourages people to support in the form of full participation in the figures, parties, struggles, and political programs offered. The audience considers the political actor as a representation/homogeneous with himself. Thus, the public/people voluntarily carry out political actions in favor of the political actors concerned. For example, among other things, the political actor is perceived as a pro-people leader.